(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
La riforma del diritto di famiglia e delle Family courts nella Repubblica di Cipro ABSTRACT: This essay addresses the 2023 amendments to Article 111 of the 1960 Constitution of the Republic of Cyprus, as well as family law reforms in the light of the religious or belief minority rights protection, promotion, and implementation. In doing so, the article relies on the findings of the Atlas of Religious or Belief minority Rights research project. The aim is to highlight how the legal system of Cyprus is slowly detaching itself from the millet logic inherited from the Ottoman past and it is further aligning with European and international standards on the protection of minority rights in different policy areas, including family law and marriage. However, religious affiliation and religious legal systems still bear significance on some issues pertaining to family law, marriage, and dissolution of marriage. SUMMARY: 1. Introduction - 2. Religious (and ethnic) affiliation in the “intractable” Constitution of the Republic of Cyprus - 3. Family courts: Article 111 of the Constitution and the Orthodox Church - 4. The Family Courts of the Religious Groups - 5. The Eighteenth Constitutional Amendment and the recent family law reforms - 6. Concluding remarks.